The Effect of Capital Structure and Dividend Policy on Firm Value with Good Corporate Governance as a Moderating Variables in Financial Sector Companies - Nikita Eka Silviana; Sri Hermuningsih; Ratih Kusumawardhani (PT SOLUSI EDUKASI BERDIKARI, 2026)
This study aims to examine the effects of capital structure (debt to asset ratio) and dividend policy (dividend payout ratio) on firm value (price to book value) for financial sector companies listed on the IDX during 2020-2024, with managerial ownership as a moderating proxy for good corporate governance. A quantitative approach using secondary annual financial statement data and purposive sampling produced 32 companies and 160 observations over five years. Data were analyzed using multiple linear regression and moderated regression analysis in SPSS 27. Result indicate that dividend payout ratio has a significant positive effect on firm value, while debt to assets ratio is not significant. Managerial ownership strengthens the positive relationship between dividend policy and firm value but does not moderate the effect between capital structure on firm value. The findings underscore the importance of dividend policy and managerial governance in enhancing firm value in Indonesian financial sector.